Depression, anxiety, stress and coping strategies among family members of patients admitted in intensive care unit in Nigeria - Oluwaseyi Isaiah Olabisi; Olaolorunpo Olorunfemi; Adetola Bolaji; Fatimah O. Azeez; Tolulope Esther Olabisi; Odunayo Azeez (Elsevier, 2020)
Background: Hospitalization of a patient in the Intensive Care Unit (ICU) negatively affects the mental health of the family caregivers and they might eventually come up with psychological disorders. This study aimed to assess the relationship between depression, anxiety, stress and coping strategies of family members of hospitalized critically ill patients. Methods: A descriptive study was conducted among 107 family members of patients admitted to ICU in Lagos State University Teaching Hospital. The Depression Anxiety Stress Scale (DASS-21) and Coping Inventory for Stressful Situation (CISS-21) were administered to the respondents. Data collected were analyzed using descriptive statistics, one-way analysis of variance and correlations statistics. Result: The mean scores and standard deviation of the family members' stress level is 8.7 (SD = 4.4); anxiety 8.5 (SD = 3.9) and depression 1.3 (SD = 1.9); 41% were anxious and 10% were stressed. There was a significant negative correlation between task oriented coping strategies and the mental health factors (depression; r = −0.193, p = 0.046; anxiety r = −0.456, p = 0.000, stress r = −0.485, p = 0.000). Family members who utilized emotion oriented coping strategies reportedly experienced anxiety (r = 0.450, p = 0.000) and stress (r = 0.564, p = 0.000). Age, income, nature of the family types, residential area and the level of education influenced the level of emotional distress. Conclusion: Patients' relatives of different socio-demographic characteristics such as age and family size experienced psychological distress and family members who used more task coping strategies experienced low level of depression, anxiety and stress.